A Novel Straightforward Compromising Method for Dynamic Economic and Emission Dispatch Considering Valve-Point Effect - Kasmaei, M. Pourakbari [UNESP] (2013)
This paper proposes a straightforward compromising method to determine the output power of all committed units during the scheduling time horizon. Unlike the conventional methods that work based on a constant pollution control cost (CPCC), this method works based on the system topology such as demand, minimum cost and minimum output emission of the system. In order to have a meaningful compromise between costs and emission in economic and emission dispatch (EED) problem, a flexible pollution control cost (FPCC) is proposed. Also a dynamic economic emission dispatch (DEED) approach is considered where the ramping constraints couple the scheduling hours; the inclusion of valve-point effect makes the DEED modeling more practical. The validity and effectiveness of the unproblematic FPCC approach is verified through an IEEE 30-bus test system with 6 unit for the 6-hour scheduling horizon.